مظاهر تأثير المبادلات التِّجارية بين المغرب الأوسط والسَّودان الغربي وأثرها في تحوّل البنى الاجتماعيَّة للسودان الغربي - عمامرة, خولة (University of Eloued جامعة الوادي, 2021)
الملخص: المتتبع لواقع التَّواصل بين المغرب الأوسط والسُّودان الغربي يجد أنَّ أسسه كانت تجاريَّة محضة منذ العصور القديمة، لكن بمجيء الإسلام أصبحت تحمل في طياتها أهدافاً دعويَّة فتحويَّة، بواسطة السُّلوك القُدوي الذي أدى إلى خلق حالة من التَّأثر تجلَّت في عدَّة مظاهر، كانت نتيجتها إحداثِ تحوُّلٍ في البنى الاجتماعيَّة ظاهراً وباطناً داخل مجتمع السُّودان الغربي، من اعتناق للإسلام ولحاق بركب الحضارة الإسلاميَّة. Abstract: Those who observe the reality of communication between the central Maghreb and western Sudan finds that its foundations were purely commercial since ancient times, but with the coming of Islam it had become carrying within it the goals of advocacy and conquest, by way of behavior that led to the creation of a state of influence that manifested itself in several manifestations, the result of which was a transformation in the structures Socialism, both outwardly and inwardly, within Western Sudanese society, from embracing Islam and catching up with Islamic civilization.